(untitled) (Revista de Artes Marciales Asiáticas, 2018)
Kung Fu associations are often understood as ‘families’ forming broader ‘family trees’ or lineages operating across centuries of history as well as transcultural associations. In an effort contributing to interdisciplinary martial arts studies, this paper presents data from two qualitative studies of Western practitioners of traditionalist Chinese martial arts (TCMA) in both the West and Asia by a phenomenological psychologist and an anthropological sociologist. We assess the use of the term ‘Kung Fu family’, what it means to the practitioners and how it impacts on their practice and their relationships with other martial artists. We argue that the conceptual metaphor of family offers a sense of belonging and solidarity within a diverse community in terms of age, ethnicity, gender, religion and social class. Meanwhile, we explore the metaphor in terms of the micro-political power dynamics that accompany martial arts collectives. Overall, the ideal of family can illuminate how identity can transcend across time (‘generations’ of practitioners) and place (from and to cultures and contingents). It is thus a way of understanding the organisation, spread and transcendence of Chinese martial arts.